Survey of the Bru1 gene for brown rust resistance in Brazilian local and basic sugarcane germplasm - Neuber, Ana Caroline [UNESP]; Camilo dos Santos, Fernanda Raquel; da Costa, Juliana Borges; Volpin, Maicon; Xavier, Mauro Alexandre; Perecin, Dilermando [UNESP]; Villavicencio Burbano, Roberto Carlos [UNESP]; Landell, Marcos Guimarães de Andrade; Pinto, Luciana Rossini (Wiley, 2017)
Bru1 is currently the major gene conferring brown rust resistance in sugarcane, and diagnostic markers are available. A survey for the presence of this gene was conducted on 391 genotypes including Brazilian cultivars, clones and basic germplasm. The efficiency of these markers for identifying resistant cultivars and artificially inoculated basic germplasm was also evaluated. The Bru1 frequency among cultivars (73.5%) suggests this gene is the prevalent source of brown rust resistance in Brazilian sugarcane breeding programmes. Most of the cultivars known to be resistant were positive for Bru1, although other genes for resistance could be present in lines not having Bru1. Only 17.8% of the basic germplasm accessions were positive for the Bru1 gene, and a low correlation between Bru1 diagnostic markers and brown rust severity was observed for basic germplasm accessions. Overall, Bru1 diagnostic markers proved to be efficient identifying resistant cultivars and clones and have potential to be in screening brown rust resistance in Brazilian breeding programmes.
Keywords: disease resistance; molecular markers; Puccinia melanocephala